Developments in Border and Migration Management in the South East European Region - POLGÁR István (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
The European Union’s South Eastern border region, and bordering countries are representing a so-called epicenter of the migration process. Basically, it is one of the main migration routes, also called the Western Balkan track, used by thousands of migrants and refugees on their way to the EU member states. Managing migration in the EU and in the neighboring countries is a social and economic investment that enables societies to strengthen their cohesion and resilience and become more prosperous. It can be considered also a societal process in which the responsibility does not rest with a specific group, but with several. The increased and more complex mixed migration movements from recent years have placed additional pressure on the already strained capacities of the authorities dealing with migration management. This extra pressure led to difficulties in terms of effectively manage the borders and address arising border security issues. The study aims to realize an inventory of the measures, proposals and activities which had an impact on transnational institution building which focuses on migration and border management.